Synthesis and Aggregation‐Induced Emission of Polyamide‐Amines as Fluorescent Switch Controlled by Hg2+‐Glutathione. Issue 13 (30th March 2022) - Zhao, Ronghui; Zheng, Jinxin; Chen, Zhuo; Wang, Meng; Zhang, Da; Ding, Lan; Fu, Congcong; Zhang, Chunfang; Deng, Kuilin
Abstract: In this study, a series of polyamide‐amines (PAAs) were prepared by Michael addition reaction of piperazine derivatives with N, N‐ bisacrylamidepiperazine (BAP). An obvious aggregation‐induced emission (AIE) effect was observed for PAAs with fluorescence emission at 425–525 nm and affected by the structure, excitation wavelength, pH value, temperature, PAAs concentration and precipitant (acetone). The piperazine rings and amides groups on PAAs backbone contribute to their AIE by the clusterization‐triggered emission (CTE) mechanism, in accordance with the red‐shift of time‐dependent density functional theory (DFT). The DFT results proved the influence of packing way on aggregation luminescence, clarified the cluster mechanism of luminescences, and the ultraviolet absorption spectrum of PAAs. Additionally, based on the coordination, Hg 2+ ions effectively quenched the fluorescence intensity of PAAs and showed enhanced quenching effect with the increase of concentration of Hg 2+ ions. And also, a reducing agent, glutathione, can restore the fluorescence of PAAs solution mixed with Hg 2+ ions, by which realizes the reversible switching process between fluorescence on and fluorescence off. Abstract : AIE‐active polyamide‐amines (PAAs) were prepared by Michael addition reaction of piperazine derivatives with N, N ‐ bisacrylamidepiperazine. The intramolecular aggregation of piperazine rings and amides on PAAs backbone plays a major role in its AIE characteristics. DFT results indicated the influence of packing way on electronic structure, and the spectral change of PAAs. Additionally, Hg 2+ ions along with glutathione realize the reversible switching process of fluorescence on and off for PAAs solution.